Study on leveraging wind farms' robust reactive power range for uncertain power system reactive power optimization. (15th September 2021) - Zhou, Yu; Li, Zhengshuo; Wang, Guangrui
Highlights: Establish a framework of utilizing wind farms as reactive power resources. Evaluate wind farms' robust reactive power range considering wind farm uncertainty. Develop an evaluation method compromising computational overheads and accuracy. Method for reactive power range-involved uncertain reactive power optimization. Enhance the safety and optimality of power grids short of reactive power resources. Abstract: This paper suggests leveraging the reactive power range embedded in wind farms to improve safety and optimality during the power system reactive power optimization process. First, three typical reactive power range approaches are analysed, and a two-stage robust linear optimization-based reactive power range evaluation method is proposed. This method yields a reactive power range that can be leveraged by an upstream system operator while ensuring wind farm operational security against wind farm uncertainty. Simplified DistFlow equations are employed to balance computational accuracy and cost. Next, an uncertain reactive power optimization problem that involves the wind farm reactive power range is introduced, through which system operators ensure system-wide security and optimality in the base case and against any possible deviation caused by system-wide load uncertainty and uncertain renewable generation. Steady-state models of automatic generation control and local voltage control against deviations are captured. This uncertain reactive power optimization problem is recast as a deterministic optimization problem that is readily solvable. Case studies confirm that even with notable uncertainty, wind farms are competent reactive power resources that provide a considerable reactive power range.